PHEROMONE TRAP CATCH OF THE HARMFUL MICROLEPIDOPTERA SPECIES DEPENDING ON THE OZONE CONTENT OF THE AIR IN HUNGARY (Acta Entomologica Serbica, 2012)
The study deals the efficiency of pheromone trapping of the seven harmful Microlepidoptera species depending on the ozone content of air. Between 2004 and 2011 Csalomon type pheromone traps were operating in Bodrogkisfalud (48°10’ N, 21°21’ E; Borsod-Abaúj-Zemplén County, Hungary, Europe). We calculated relative catch values from the number of caught insects. We assigned these to the ozone values, we averaged them, and we depicted the results together with the regression equation though.  We established that the pheromone trapping of this species is most fruitful when the ozone content of the air is high. By contrast, low ozone values reduce the successfulness of the catching to a moderate level. Our results will be exploitable in plant protecting and environment conservation research.